ANALYSIS OF ONLINE SHOP SITE POPULARITY IN INDONESIA - Widodo, Agus Tikno (Penerbit Atma Jaya Catholic University of Indonesia, 2019)
This journal will analyze how to determine the type of online buying and selling e-commerce, as it is now emerging a lot of e-commerce start-ups. As one of the companies that produce cosmetic products and is currently being a switch that was originally sold in stores, malls, supermarkets, and other physical stores, want to do business online, especially in the field of e-commerce. Thus, in the discussion will be discussed how to understand this business and determine the cooperation with e-commerce that best suits the cosmetic business today. There are 4 types of E-commerce business classification: B2B (Business to Business), B2C (Business to Consumer), C2B (Consumer to Business), C2C (Consumer to Consumer).